Error performance enhancement and complexity reduction in OFDM systems via coordinate interleaving under practical impairments - Reşat, Mustafa Anıl; Tusha, Armed; Doğan Tusha, Seda; Özyurt, Serdar; Arslan, Hüseyin (Turkiye Klinikleri, 2024)
In this work, subcarrier coordinate interleaving (CI) is implemented to orthogonal frequency division multiplexing (OFDM) systems with the aim of both enhancing the error performance and reducing the implementation complexity. To this end, the modulated symbols are independently chosen from a modified M-ary amplitude-shift keying signal constellation under a specific CI strategy. In addition to doubling the diversity level of the original OFDM scheme, the adopted CI approach also drastically reduces the inverse fast Fourier transform (IFFT) size at the transmit side by guaranteeing the first half of the input vector to be identical with the second half at the input to the IFFT block. It is further demonstrated that the proposed system has the ability to enhance the robustness against common practical impairments such as insufficient cyclic prefix and phase noise. The closed-form expression of symbol error probability of the system is derived and confirmed with the simulation results.
Keywords: Orthogonal Frequency Division Multiplexing; Signal Space Diversity; Coordinate Interleaving; Intersymbol Interference; Phase Noise